2022
DOI: 10.3390/su141912499
|View full text |Cite
|
Sign up to set email alerts
|

Complex Cause-Effect Relationships of Social Capital, Leader-Member Exchange, and Safety Behavior of Workers in Small-Medium Construction Firms and the Moderating Role of Age

Abstract: Due to workers’ vulnerability in construction sites, workplace safety has become of particular interest, and the current literature offers myriad approaches to dealing with it. From a social and organizational lens, this study explores an empirical model that integrates the dimensions of social capital theory (SCT) and leader-member exchange (LMX) in modelling the safety behavior of construction workers, particularly relevant in small-medium construction firms. The data were collected from 232 construction wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…However, adopting optimization methods or sampling techniques, such as taking an unbiased random walk inside the graph space, would reduce the computational cost of the GCN algorithm. (6) The developed construction safety model could be enhanced to predict construction risks based on project type, along with other input attributes, such as the age and experience of the worker, the activity performed, and workplace and human factors. This would allow construction professionals to evaluate different accident scenarios and flag high-risk accident scenarios while considering dependency information based on the construction project type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adopting optimization methods or sampling techniques, such as taking an unbiased random walk inside the graph space, would reduce the computational cost of the GCN algorithm. (6) The developed construction safety model could be enhanced to predict construction risks based on project type, along with other input attributes, such as the age and experience of the worker, the activity performed, and workplace and human factors. This would allow construction professionals to evaluate different accident scenarios and flag high-risk accident scenarios while considering dependency information based on the construction project type.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some improvements in the sector and years of effort put into risk minimization, the situation regarding occupational safety and health (OSH)-related injuries and fatalities remains alarming [1] and is a constant concern [2], displaying high incident rates [3][4][5]. Research has focused on workplace safety, due to the vulnerable position of construction workers [6].…”
Section: Introductionmentioning
confidence: 99%
“…A clear organizational structure with well-defined rules and regulations is one of the effective means to reduce the leader–member exchange ambivalence [ 29 ], but this ambivalence is difficult to erase completely. The leader–member exchange ambivalence is an implicit factor that cannot be precisely described using a single indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Su et al [37] showed that LMX has significant effects on different types of safety violations through attitudinal ambivalence, group safety norm, and perceived behavioral control. However, [38] indicated that LMX directly influences safety participation but does not significantly impact safety compliance.…”
Section: ) Leader-member Exchange (Lmx) and Cwsbmentioning
confidence: 98%